Synergistic effect of social support and self-efficacy on physical exercise in older adults - Warner, Lisa M.; Ziegelmann, Jochen P.; Schüz, Benjamin; Wurm, Susanne; Schwarzer, Ralf (Journal of aging and physical activity, 2011)
The purpose of the current study was to examine whether the effects of social support on physical exercise in older adults depend on individual perceptions of self-efficacy. Three hundred nine older German adults (age 65-85) were assessed at 3 points in time (3 months apart). In hierarchical-regression analyses, support received from friends and exercise self-efficacy were specified as predictors of exercise frequency while baseline exercise, sex, age, and physical functioning were controlled for. Besides main effects of self-efficacy and social support, an interaction between social support and self-efficacy emerged. People with low selfefficacy were less likely to be active in spite of having social support. People with low support were less likely to be active even if they were high in self-efficacy. This points to the importance of both social support and self-efficacy and implies that these resources could be targets of interventions to increase older adults' exercise. © 2011 Human Kinetics, Inc.
Keywords: Exercise-specific self-efficacy; Exercise-specific social support; Multimorbidity; Social-cognitive theory; Sources of exercise support